Program Layanan Bimbingan Belajar untuk Peserta Didik Berkesulitan Belajar Matematika Kelas III SDN Tapos 2 - Ara Meilia Rahmayani; Fatihaturosyidah; Tatang Suratno (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
The background of this research is based on observations during real work lectures (KKN) and practice of microteaching courses. Researchers found an interesting phenomenon, namely the discovery of students in class III who have difficulty learning mathematics, especially regarding number operations. Therefore, it is necessary to have a tutoring service program which is an activity carried out structurally in serving and guiding students who are still having difficulties in learning. The problem discussed in this study is a program design for tutoring services needed for students with learning difficulties in mathematics. The purpose of this study is to make recommendations for tutoring programs according to the needs for students who have difficulty learning math class III at SD Negeri Tapos 2. Because in learning activities while in class, there are still students who still do not understand the basic concepts of number operations and cannot distinguish operational symbols in a mathematical sentence. The approach used in this research is a qualitative approach with a case study method. This method is carried out with data collection techniques through observation, interviews, and documentation to obtain data and information through direct observations and sources. From the findings that have been analyzed, that students who have learning difficulties in mathematics need a tutoring service which includes a monthly program of tutoring services in the form of a matrix, as well as evaluation of questions. So that the process of learning activities for students who have difficulty learning mathematics can be served and run well according to their needs.